Feeding interactions between the deer, Odocoileus virginianus (Mammalia: Cervidae) and four species of birds in Costa Rica (UNED Research Journal, 2020)
Introduction: Mammalian-bird interactions are poorly known in the tropics. Methods: To analyze the inteactions between White-tailed Deer and birds I noted and photographed interactions in the tropical humid forest of Curú, Costa Rica, between July 2005 and October 2019. Results: The most common interaction was with the Groove-billed Ani (82 % of all observations), followed by the White-throated Magpie-Jay (10%), Crested Caracara (5%) and Yellow-headed Caracara (3%). Conclusion: Although some of these interrelationships had already been reported in other locations, these results are new for Costa Rica.
Keywords: Comensalism; Protocooperation; White-tailed deer; Birds